Oral and Topical Sirolimus for Vascular Anomalies: A Multicentre Study and Review - Shira Sandbank; Vered Molho-Pessach; Adam Farkas; Aviv Barzilai; Shoshana Greenberger (Medical Journals Sweden, 2019)
Vascular anomalies (VAs) may be associated with significant morbidity and mortality. The aim of this study was to evaluate the efficacy and safety of sirolimus (rapamycin) in the treatment of children and young adults with complicated VAs. A retrospective chart was created that included 19 patients treated with sirolimus for complicated VAs. Concurrently, a search of the PubMed database for VA cases treated with sirolimus was conducted. Descriptive analysis was performed and the efficiency rate of sirolimus was calculated. This retrospective study included 19 patients, 17 of whom were treated with oral sirolimus and 2 with topical sirolimus. Clinical improvement occurred in 15 patients (79%). One patient experienced near-complete resolution. Only 2 patients showed poor response and discontinued treatment. The literature review analysed 150 cases of VA treated with sirolimus. Sirolimus was efficient in 85% of cases, including 5 cases of complete resolution. Sirolimus appears to be an effective and safe treatment for children and young adults with complicated VAs.